Rubber material, preparation method thereof and packer rubber sleeve based on rubber material

By using new rubber materials and a second-stage vulcanization process in the packer rubber cylinder, the problem of existing rubber cylinders being easily expanded and aging in crude oil environment is solved, and the productization of rubber cylinders with high cost performance and high resistance is achieved, which extends the service life.

CN119661913AActive Publication Date: 2025-03-21CHINA NAT PETROLEUM CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311233460.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-03-21
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

The existing packer rubber barrels are prone to expand in crude oil environments, and the underground high temperature and high pressure and corrosion environments cause the rubber barrel to relax and age, increase hardness, decrease elasticity, and decrease strength, shorten service life.

Method used

A new type of rubber material, including hydrogenated nitrile rubber, carbon black, anti-aging agent RD (TMQ) or its mixture with SP, plasticizer and peroxide vulcanizer, is used to prepare a high cost-effective and high resistance packer rubber cylinder through multiple mixing and plasticizing of the mixer and the first and second stage vulcanization processes.

Benefits of technology

The rubber material significantly improves the aging performance and tension elongation of the rubber tube by adding anti-aging agents and plasticizers. The second-stage vulcanization process further improves the overall performance of the material, making the rubber tube more stable under strict downhole conditions and prolongs its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004464761570000051
    Figure BDA0004464761570000051
  • Figure BDA0004464761570000061
    Figure BDA0004464761570000061
  • Figure BDA0004464761570000071
    Figure BDA0004464761570000071
Patent Text Reader

Abstract

The invention provides a rubber material and a preparation method thereof, and a packer rubber cylinder based on the rubber material, the rubber material comprises the following components by mass: 100 parts of hydrogenated nitrile rubber, 60-70 parts of carbon black, 2 parts of an anti-aging agent, 0.5 part of a plasticizer, and 6.5-7.0 parts of a peroxide vulcanizing agent; the anti-aging agent is RD (TMQ) or a mixture of the RD (TMQ) and styrenated phenol. According to the rubber material, the anti-aging agent RD (TMQ) or the mixture of RD (TMQ) and styrenated phenol is added, a very good anti-aging effect can be achieved, especially when RD (TMQ) and SP are combined for use, the aging performance of the rubber material can be further improved, it is indicated that when RD (TMQ) and SP are combined for use, a certain synergistic effect can be achieved, and the overall performance of the rubber material meets related standard requirements. When the rubber material provided by the invention is used for preparing the packer rubber cylinder, productization of high-cost-performance and high-resistance rubber cylinders can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of elastomeric materials and relates to a rubber material and a preparation method thereof and a packer rubber cylinder based on the rubber material. Background Art

[0002] The packer is an elastic sealing element located between the casing and the tubing, which is of great significance for the production of oil and gas. The main functions of the packer include: (1) isolating the production layer or target layer to prevent the fluid and pressure between the layers from interfering with each other; (2) ensuring the pressure of the sealing layer and improving the production efficiency of the oil well; (3) cooperating with the operations of casing inspection, leak detection, acid fracturing, water injection, well washing, etc.

[0003] The packer itself is composed of steel parts and rubber cylinders. The rubber cylinder is a key component of the packer. Its development has gone through metal, asbestos, and now elastomeric materials, including rubber products and plastics. At present, the rubber cylinders with a high market share are mainly based on ethylene propylene diene monomer rubber (EPDM), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), fluororubber (FKM), etc. During use, it was found that the packer rubber cylinders based on EPDM and NBR are very easy to expand in the crude oil environment. Coupled with the high temperature, high pressure and corrosive environment downhole, the rubber cylinders gradually relax and age, which is manifested as increased hardness, decreased elasticity, and reduced strength, shortening the service life. HNBR and FKM, relatively speaking, have better oleophobicity and can better slow down the penetration of corrosive gases and liquids, so they are used in the preparation of packer rubber cylinders. Among them, FKM has a deviation in processability and a higher price. Therefore, for harsh downhole working conditions, HNBR rubber cylinders are generally used.

[0004] At present, II-80 type (II represents the mixed rubber with hydrogenated nitrile as the main body, and 80 represents the Shore hardness of the rubber cylinder) packer rubber cylinder has a large market usage, but the performance varies greatly and needs further improvement. Summary of the invention

[0005] In order to solve the above problems of the prior art, the present invention provides a rubber material and a preparation method thereof and a packer rubber cartridge based thereon. The rubber material of the present invention can realize the production of a rubber cartridge with high cost performance and high durability.

[0006] The present invention is achieved through the following technical solutions:

[0007] A rubber material comprises, by weight, 100 parts of hydrogenated nitrile rubber, 60-70 parts of carbon black, 2 parts of an antioxidant, 0.5 parts of a plasticizer, and 6.5-7.0 parts of a peroxide vulcanizer; the antioxidant is RD (TMQ), or a mixture of RD (TMQ) and styrenated phenol.

[0008] Preferably, when the antioxidant is a mixture of RD (TMQ) and SP, the ratio of RD (TMQ) to SP is 1:2.

[0009] Preferably, the carbon black is carbon black N220.

[0010] Preferably, the plasticizer is dioctyl terephthalate.

[0011] Preferably, the peroxide curing agent is di-tert-butyl peroxide isopropylbenzene.

[0012] The method for preparing the rubber material comprises:

[0013] The hydrogenated nitrile rubber is kneaded; part of carbon black, part of antioxidant and part of plasticizer are added and kneaded; the remaining carbon black, antioxidant and plasticizer are added, kneaded, and rubber is discharged to obtain a rubber compound;

[0014] The rubber material is plasticized; a portion of the peroxide vulcanizer is added and plasticized; and the remaining vulcanizer is added and plasticized;

[0015] The plasticized rubber compound undergoes one-stage vulcanization and two-stage vulcanization.

[0016] Preferably, the time for one vulcanization period is 8.77 to 10.77 minutes.

[0017] Preferably, the plasticizing temperature is 45-50°C.

[0018] Preferably, a vulcanization curve test is performed on the plasticized rubber material, and a stage of vulcanization is performed on the plasticized rubber material according to the test result.

[0019] A packer rubber cylinder is made of the rubber material mentioned above.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The rubber material based on hydrogenated nitrile rubber of the present invention is added with an anti-aging agent RD (TMQ) or a mixture of RD (TMQ) and SP (styrenated phenol), which can play a good anti-aging effect. In particular, when RD (TMQ) and SP are used in combination, the aging performance of the rubber material can be further improved, indicating that the combination of RD (TMQ) and SP can play a certain synergistic role. The addition of carbon black can improve the hardness of the rubber material, and the addition of plasticizer can improve the elongation at break of the rubber material. The overall performance of the rubber material of the present invention meets the requirements of relevant standards.

[0022] Furthermore, when RD(TMQ) / SP=1:2, the performance of the rubber material is the best, which is significantly better than the performance of RD(TMQ) and SP alone as antioxidants.

[0023] The preparation method of the rubber material of the present invention performs two-stage vulcanization on the mixed rubber. Experimental results show that the material performance obtained by the two-stage vulcanization is better than the material performance obtained by the one-stage vulcanization, which shows that the two-stage vulcanization is crucial to the preparation of the rubber material of the present invention.

[0024] The rubber material of the present invention is used to prepare a packer rubber cartridge, so as to realize the production of a rubber cartridge with high cost performance and high durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the vulcanization curve of the rubber compound obtained after plasticating on the open mill in Example 1. DETAILED DESCRIPTION

[0026] In order to further understand the present invention, the present invention is described below in conjunction with embodiments. These descriptions are only to further explain the features and advantages of the present invention and are not intended to limit the claims of the present invention.

[0027] The rubber material of the present invention comprises, by weight, 100 parts of hydrogenated nitrile rubber, 60-70 parts of carbon black, 2 parts of antioxidant, 0.5 part of plasticizer, and 6.5-7.0 parts of peroxide vulcanizer; the antioxidant is RD (TMQ), or a mixture of RD (TMQ) and SP.

[0028] The carbon black is preferably carbon black N220, the plasticizer is preferably dioctyl terephthalate, and the peroxide curing agent is preferably di-tert-butyl peroxide isopropylbenzene. When the antioxidant is a mixture of RD (TMQ) and SP, the ratio of RD (TMQ) to SP is preferably 1:2.

[0029] The method for preparing the rubber material of the present invention comprises:

[0030] Using an internal mixer, adding hydrogenated nitrile rubber and mixing; adding part of carbon black, antioxidant and plasticizer and mixing; adding the remaining carbon black, antioxidant and plasticizer, mixing, and rubber removal to obtain a rubber compound;

[0031] Adjust the roller temperature of the open mixer to 45-50℃, the roller distance to 1.0mm, plasticize the rubber material taken out from the internal mixer to make it into sheets, and then adjust the roller distance to 0.1-0.15mm; refining several times, adding 1 / 2 equivalent vulcanizing agent, refining several times, then adding the remaining vulcanizing agent, refining several times; rolling several times, unrolling; after standing, conduct vulcanization curve test;

[0032] Vulcanize on a flat vulcanizer for 8.77 to 10.77 minutes, let it stand, carry out second-stage vulcanization, take out the rubber material, and let it stand at room temperature.

[0033] The rubber material can be used to prepare a rubber sleeve of a packer.

[0034] This is illustrated by the following examples.

[0035] Example 1

[0036] 100 parts of hydrogenated nitrile rubber, 70 parts of carbon black N220, 2 parts of antioxidant RD (TMQ), 0.5 parts of plasticizer dioctyl terephthalate (DOTP), and 6.5 parts of peroxide curing agent di-tert-butyl peroxide isopropylbenzene (BIPB).

[0037] Sample preparation:

[0038] Use a 200mL internal mixer, adjust the starting temperature to 50°C and the speed to 40rpm. Lift the top plug, add the hydrogenated nitrile rubber within 15 seconds, close the top plug, and mix for 60 seconds. Lift the top plug, add 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Lift the top plug again, add the remaining 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Mix for another 60 seconds, discharge the rubber, and obtain the rubber compound.

[0039] Take out the rubber compound from the internal mixer and weigh it. Compare it with the total mass of all raw materials added to the internal mixer. The rubber compound loss should be controlled within 3%. Adjust the roller temperature of the open mixer to 45°C and the roller distance to 1.0mm. Plasticize the rubber compound taken out from the internal mixer to make it into sheets, and then adjust the roller distance to 0.12mm. First, turn over three times, add 1 / 2 equivalent vulcanizer, turn over three times, then add the remaining vulcanizer, and turn over three times. Roll 6 times and take off the sheet. After standing for 16 hours, perform the vulcanization curve test.

[0040] Through the rotorless vulcanizer test, it was determined that when the vulcanization temperature was 175°C, t 10 =0.58min, t 90 =6.77min, Figure 1 It is the vulcanization curve of the rubber compound obtained after plastication on the open mill. Vulcanize in a flat vulcanizer for 8.77 minutes, let stand for 4 hours, perform a second stage vulcanization at 150℃×4 hours, take out the rubber compound, and let stand at room temperature for 16 hours. Cut the rubber compound into dumbbell-shaped specimens and conduct relevant performance tests according to "HG / T2701-2016 Compression Packer Rubber Cylinder". The test results are shown in Table 1.

[0041] Table 1 Test results of physical properties of rubber compound in Example 1

[0042]

[0043]

[0044] Table 1 is the test results of the physical properties of the rubber compound of Example 1, and all test results meet the requirements of relevant standards.

[0045] Example 2

[0046] 100 parts of hydrogenated nitrile rubber, 70 parts of carbon black N220, 2 parts of antioxidant RD (TMQ), 0.5 parts of plasticizer DOTP, and 7.0 parts of peroxide vulcanizing agent BIPB.

[0047] Sample preparation:

[0048] Use a 200mL internal mixer, adjust the starting temperature to 50°C and the speed to 40rpm. Lift the top plug, add the hydrogenated nitrile rubber within 15 seconds, close the top plug, and mix for 60 seconds. Lift the top plug, add 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Lift the top plug again, add the remaining 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Mix for another 60 seconds, discharge the rubber, and obtain the rubber compound.

[0049] Take out the rubber compound from the internal mixer and weigh it. Compare it with the total mass of all raw materials added to the internal mixer. The rubber compound loss should be controlled within 3%. Adjust the roller temperature of the open mixer to 45°C and the roller distance to 1.0mm. Plasticize the rubber compound taken out from the internal mixer to make it into sheets, and then adjust the roller distance to 0.12mm. First, turn over three times, add 1 / 2 equivalent vulcanizer, turn over three times, then add the remaining vulcanizer, and turn over three times. Roll 6 times and take off the sheet. After standing for 16 hours, perform the vulcanization curve test.

[0050] Through the rotorless vulcanizer test, it was determined that when the vulcanization temperature was 175°C, t 90 =6.77min. Vulcanize in a flat vulcanizer for 8.77min, let stand for 4h, perform a second stage vulcanization at 150℃×4h, take out the rubber material, and let stand at room temperature for 16h. Cut the rubber material into dumbbell-shaped specimens and perform relevant performance tests according to "HG / T 2701-2016 Compression Packer Rubber Cylinder". The test results are shown in Table 2.

[0051] Table 2 Physical properties test results of rubber compound in Example 2

[0052]

[0053] As shown in Table 2, compared with Example 1, Example 2 adds 0.5 parts of BIPB, resulting in a significant increase in the change rate of elongation at break after hot air aging, which indicates that the amount of plasticizer used has a great influence on the performance of the compound rubber.

[0054] Example 3

[0055] 100 parts of hydrogenated nitrile rubber, 60 parts of carbon black N220, 2 parts of antioxidant RD (TMQ), 0.5 parts of plasticizer DOTP, and 7.0 parts of peroxide vulcanizing agent BIPB.

[0056] Sample preparation:

[0057] Use a 200mL internal mixer, adjust the starting temperature to 50°C and the speed to 40rpm. Lift the top plug, add the hydrogenated nitrile rubber within 15 seconds, close the top plug, and mix for 60 seconds. Lift the top plug, add 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Lift the top plug again, add the remaining 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Mix for another 60 seconds, discharge the rubber, and obtain the rubber compound.

[0058] Take out the rubber compound from the internal mixer and weigh it. Compare it with the total mass of all raw materials added to the internal mixer. The rubber compound loss should be controlled within 3%. Adjust the roller temperature of the open mixer to 45°C and the roller distance to 1.0mm. Plasticize the rubber compound taken out from the internal mixer to make it into sheets, and then adjust the roller distance to 0.12mm. First, turn over three times, add 1 / 2 equivalent vulcanizer, turn over three times, then add the remaining vulcanizer, and turn over three times. Roll 6 times and take off the sheet. After standing for 16 hours, perform the vulcanization curve test.

[0059] Through the rotorless vulcanizer test, it was determined that when the vulcanization temperature was 175°C, t 90 =6.77min. Vulcanize in a flat vulcanizer for 8.77min, let stand for 4h, perform a second stage vulcanization at 150℃×4h, take out the rubber material, and let stand at room temperature for 16h. Cut the rubber material into dumbbell-shaped specimens and perform relevant performance tests according to "HG / T 2701-2016 Compression Packer Rubber Cylinder". The test results are shown in Table 3.

[0060] Table 3 Physical properties test results of the rubber compound of Example 3

[0061]

[0062] Compared with Example 1, Example 3 reduces the amount of carbon black N220 used (reduced by 10 parts). As shown in Table 3, the hardness of the mixed rubber is slightly reduced, and the tensile strength and elongation at break are significantly increased.

[0063] Example 4

[0064] 100 parts of hydrogenated nitrile rubber, 60 parts of carbon black N220, 2 parts of antioxidant RD (TMQ), 0.5 parts of plasticizer DOTP, and 6.5 parts of peroxide vulcanizing agent BIPB.

[0065] Sample preparation:

[0066] Use a 200mL internal mixer, adjust the starting temperature to 50°C and the speed to 40rpm. Lift the top plug, add the hydrogenated nitrile rubber within 15 seconds, close the top plug, and mix for 60 seconds. Lift the top plug, add 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Lift the top plug again, add the remaining 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Mix for another 60 seconds, discharge the rubber, and obtain the rubber compound.

[0067] Take out the rubber compound from the internal mixer and weigh it. Compare it with the total mass of all raw materials added to the internal mixer. The rubber compound loss should be controlled within 3%. Adjust the roller temperature of the open mixer to 45°C and the roller distance to 1.0mm. Plasticize the rubber compound taken out from the internal mixer to make it into sheets, and then adjust the roller distance to 0.12mm. First, turn over three times, add 1 / 2 equivalent vulcanizer, turn over three times, then add the remaining vulcanizer, and turn over three times. Roll 6 times and take off the sheet. After standing for 16 hours, perform the vulcanization curve test.

[0068] Through the rotorless vulcanizer test, it was determined that when the vulcanization temperature was 175°C, t 90 =6.77min. Vulcanize in a flat vulcanizer for 8.77min, let stand for 4h, perform a second stage vulcanization at 150℃×4h, take out the rubber material, and let stand at room temperature for 16h. Cut the rubber material into dumbbell-shaped specimens and perform relevant performance tests according to "HG / T 2701-2016 Compression Packer Rubber Cylinder". The test results are shown in Table 4.

[0069] Table 4 Physical properties test results of rubber mix in Example 4

[0070]

[0071]

[0072] Compared with Example 1, Example 4 has a certain reduction in the amount of carbon black and BIPBN used, resulting in a significant change in the elongation at break of the mixed rubber. At the same time, the variability of the elongation at break after hot air aging and the compression permanent deformation tend to deteriorate.

[0073] Example 5

[0074] 100 parts of hydrogenated nitrile rubber, 65 parts of carbon black N220, 2 parts of antioxidant RD (TMQ), 0.5 parts of plasticizer DOTP, and 7.0 parts of peroxide vulcanizing agent BIPB.

[0075] Sample preparation:

[0076] Use a 200mL internal mixer, adjust the starting temperature to 50°C and the speed to 40rpm. Lift the top plug, add the hydrogenated nitrile rubber within 15 seconds, close the top plug, and mix for 60 seconds. Lift the top plug, add 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Lift the top plug again, add the remaining 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Mix for another 60 seconds, discharge the rubber, and obtain the rubber compound.

[0077] Take out the rubber compound from the internal mixer and weigh it. Compare it with the total mass of all raw materials added to the internal mixer. The rubber compound loss should be controlled within 3%. Adjust the roller temperature of the open mixer to 48°C and the roller distance to 1.0mm. Plasticize the rubber compound taken out from the internal mixer to make it into sheets, and then adjust the roller distance to 0.15mm. First, turn over three times, add 1 / 2 equivalent vulcanizer, turn over three times, then add the remaining vulcanizer, and turn over three times. Roll 6 times and take off the sheet. After standing for 16 hours, perform the vulcanization curve test.

[0078] Through the rotorless vulcanizer test, it was determined that when the vulcanization temperature was 175°C, t 90 =6.97min. Vulcanize in a flat vulcanizer for 8.97min, let stand for 4h, perform a second stage vulcanization at 150℃×4h, take out the rubber material, and let stand at room temperature for 16h. Cut the rubber material into dumbbell-shaped specimens and perform relevant performance tests according to "HG / T 2701-2016 Compression Packer Rubber Cylinder". The test results are shown in Table 5.

[0079] Table 5 Physical properties test results of the rubber compound of Example 5

[0080]

[0081] As can be seen from the table above, the roll distance has a certain influence on the vulcanization time. Compared with Example 1 and Example 2, the amount of carbon black has an influence on the elongation at break, compression set, etc.

[0082] Example 6

[0083] 160 parts of hydrogenated nitrile rubber, 112 parts of carbon black N220, 3.2 parts of antioxidant RD (TMQ), 0.8 parts of plasticizer DOTP, and 11.2 parts of peroxide vulcanizing agent BIPB.

[0084] Sample preparation:

[0085] Use a 500mL internal mixer, adjust the starting temperature to 50°C and the speed to 40rpm. Lift the top plug, add the hydrogenated nitrile rubber within 15 seconds, close the top plug, and mix for 60 seconds. Lift the top plug, add 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Lift the top plug again, add the remaining 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Mix for another 60 seconds, discharge the rubber, and obtain the rubber compound.

[0086] Take out the rubber compound from the internal mixer and weigh it. Compare it with the total mass of all raw materials added to the internal mixer. The rubber compound loss should be controlled within 3%. Adjust the roller temperature of the open mixer to 50°C and the roller distance to 1.0mm. Plasticize the rubber compound taken out from the internal mixer to make it into sheets, and then adjust the roller distance to 0.12mm. First, turn over three times, add 1 / 2 equivalent vulcanizer, turn over three times, then add the remaining vulcanizer, and turn over three times. Roll 6 times and take off the sheet. After standing for 16 hours, perform the vulcanization curve test.

[0087] Through the rotorless vulcanizer test, it was determined that when the vulcanization temperature was 175°C, t 90 =6.72min. Vulcanize in a flat vulcanizer for 9.72min, let stand for 4h, perform a second stage vulcanization at 150℃×4h, take out the rubber material, and let stand at room temperature for 16h. Cut the rubber material into dumbbell-shaped specimens and perform relevant performance tests according to "HG / T 2701-2016 Compression Packer Rubber Cylinder". The test results are shown in Table 6.

[0088] Table 6 Physical properties test results of the rubber compound of Example 6

[0089]

[0090] Compared with Example 1, the synthesis amount of the rubber mix in Example 6 is increased by 1.6 times. The test results in Table 6 show that the increase in the synthesis amount does not affect the related properties of the rubber mix.

[0091] Example 7

[0092] 200 parts of hydrogenated nitrile rubber, 140 parts of carbon black N220, 4 parts of antioxidant RD (TMQ), 1.0 parts of plasticizer DOTP, and 13 parts of peroxide vulcanizing agent BIPB.

[0093] Sample preparation

[0094] Use a 500mL internal mixer, adjust the starting temperature to 50°C and the speed to 40rpm. Lift the top plug, add the hydrogenated nitrile rubber within 15 seconds, close the top plug, and mix for 60 seconds. Lift the top plug, add 1 / 3 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Lift the top plug again, add 1 / 3 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Lift the top plug again, add the remaining 1 / 3 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Mix for another 60 seconds, discharge the rubber, and obtain the rubber compound.

[0095] Take out the rubber compound from the internal mixer and weigh it. Compare it with the total mass of all raw materials added to the internal mixer. The rubber compound loss should be controlled within 3%. Adjust the roller temperature of the open mixer to 50°C and the roller distance to 1.0mm. Plasticize the rubber compound taken out from the internal mixer to make it into sheets, and then adjust the roller distance to 0.12mm. First, turn over three times, add 1 / 2 equivalent vulcanizer, turn over three times, then add the remaining vulcanizer, and turn over three times. Roll 6 times and take off the sheet. After standing for 16 hours, perform the vulcanization curve test.

[0096] Through the rotorless vulcanizer test, it was determined that when the vulcanization temperature was 175°C, t 90 =6.72min. Vulcanize in a flat vulcanizer for 10.72min, let stand for 4h, perform a second stage vulcanization at 150℃×4h, take out the rubber material, and let stand at room temperature for 16h. Cut the rubber material into dumbbell-shaped specimens and perform relevant performance tests according to "HG / T 2701-2016 Compression Packer Rubber Cylinder". The test results are shown in Table 7.

[0097] Table 7 Physical properties test results of rubber mix in Example 7

[0098]

[0099] Compared with Example 2, the synthesis amount of the rubber mix in Example 6 is increased by 2.0 times. The test results in Table 7 show that as the synthesis amount increases, some properties of the rubber mix (such as elongation at break) will change to a certain extent.

[0100] Comparative Example 1

[0101] 100 parts of hydrogenated nitrile rubber, 70 parts of carbon black N220, 2 parts of antioxidant SP (styrenated phenol), 0.5 parts of plasticizer dioctyl terephthalate (DOTP), 6.5 parts of peroxide curing agent di-tert-butyl peroxide isopropylbenzene (BIPB).

[0102] Sample preparation:

[0103] Use a 200mL internal mixer, adjust the starting temperature to 50°C and the speed to 40rpm. Lift the top plug, add the hydrogenated nitrile rubber within 15 seconds, close the top plug, and mix for 60 seconds. Lift the top plug, add 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Lift the top plug again, add the remaining 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Mix for another 60 seconds, discharge the rubber, and obtain the rubber compound.

[0104] Take out the rubber compound from the internal mixer and weigh it. Compare it with the total mass of all raw materials added to the internal mixer. The rubber compound loss should be controlled within 3%. Adjust the roller temperature of the open mixer to 45°C and the roller distance to 1.0mm. Plasticize the rubber compound taken out from the internal mixer to make it into sheets, and then adjust the roller distance to 0.12mm. First, turn over three times, add 1 / 2 equivalent vulcanizer, turn over three times, then add the remaining vulcanizer, and turn over three times. Roll 6 times and take off the sheet. After standing for 16 hours, perform the vulcanization curve test.

[0105] Through the rotorless vulcanizer test, it was determined that when the vulcanization temperature was 175°C, t 10 =0.58min, t 90 =6.36min, Figure 1 It is the vulcanization curve of the rubber compound obtained after plastication on the open mill. Vulcanize in a flat vulcanizer for 8.36 minutes, let stand for 4 hours, perform a second stage vulcanization at 150℃×4 hours, take out the rubber compound, and let stand at room temperature for 16 hours. Cut the rubber compound into dumbbell-shaped specimens and conduct relevant performance tests according to "HG / T2701-2016 Compression Packer Rubber Cylinder". The test results are shown in Table 8.

[0106] Table 8 Comparative Example 1 Rubber Mix Physical Properties Test Results

[0107]

[0108]

[0109] Table 8 is the test results of physical properties of the rubber mix of Example 1. Compared with Example 1, after the antioxidant was replaced with SP, some properties of the rubber mix were unqualified (compression set).

[0110] Example 8

[0111] 100 parts of hydrogenated nitrile rubber, 70 parts of carbon black N220, 2 parts of antioxidant (RD(TMQ) / SP=1 / 1), 0.5 parts of plasticizer dioctyl terephthalate (DOTP), 6.5 parts of peroxide curing agent di-tert-butyl peroxide isopropylbenzene (BIPB).

[0112] Sample preparation:

[0113] Use a 200mL internal mixer, adjust the starting temperature to 50°C and the speed to 40rpm. Lift the top plug, add the hydrogenated nitrile rubber within 15 seconds, close the top plug, and mix for 60 seconds. Lift the top plug, add 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Lift the top plug again, add the remaining 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Mix for another 60 seconds, discharge the rubber, and obtain the rubber compound.

[0114] Take out the rubber compound from the internal mixer and weigh it. Compare it with the total mass of all raw materials added to the internal mixer. The rubber compound loss should be controlled within 3%. Adjust the roller temperature of the open mixer to 45°C and the roller distance to 1.0mm. Plasticize the rubber compound taken out from the internal mixer to make it into sheets, and then adjust the roller distance to 0.12mm. First, turn over three times, add 1 / 2 equivalent vulcanizer, turn over three times, then add the remaining vulcanizer, and turn over three times. Roll 6 times and take off the sheet. After standing for 16 hours, perform the vulcanization curve test.

[0115] Through the rotorless vulcanizer test, it was determined that when the vulcanization temperature was 175°C, t 10 =0.58min, t 90 =6.47min, Figure 1 It is the vulcanization curve of the rubber compound obtained after plastication on the open mill. Vulcanize in a flat vulcanizer for 8.47 minutes, let stand for 4 hours, perform a second stage vulcanization at 150℃×4 hours, take out the rubber compound, and let stand at room temperature for 16 hours. Cut the rubber compound into dumbbell-shaped specimens and conduct relevant performance tests according to "HG / T2701-2016 Compression Packer Rubber Cylinder". The test results are shown in Table 9.

[0116] Table 9 Physical properties test results of the rubber compound in Example 8

[0117]

[0118] Table 9 is the test results of physical properties of the rubber mix of Example 8. Compared with Comparative Example 1, after the antioxidant is changed to RD(TMQ) / SP=1 / 1, the compression permanent deformation performance of the rubber mix is ​​improved, and various performance indicators meet the requirements.

[0119] Example 9

[0120] 100 parts of hydrogenated nitrile rubber, 70 parts of carbon black N220, 2 parts of antioxidant (RD(TMQ) / SP=1 / 2), 0.5 parts of plasticizer dioctyl terephthalate (DOTP), 6.5 parts of peroxide curing agent di-tert-butyl peroxide isopropylbenzene (BIPB).

[0121] Sample preparation:

[0122] Use a 200mL internal mixer, adjust the starting temperature to 50°C and the speed to 40rpm. Lift the top plug, add the hydrogenated nitrile rubber within 15 seconds, close the top plug, and mix for 60 seconds. Lift the top plug, add 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Lift the top plug again, add the remaining 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Mix for another 60 seconds, discharge the rubber, and obtain the rubber compound.

[0123] Take out the rubber compound from the internal mixer and weigh it. Compare it with the total mass of all raw materials added to the internal mixer. The rubber compound loss should be controlled within 3%. Adjust the roller temperature of the open mixer to 45°C and the roller distance to 1.0mm. Plasticize the rubber compound taken out from the internal mixer to make it into sheets, and then adjust the roller distance to 0.12mm. First, turn over three times, add 1 / 2 equivalent vulcanizer, turn over three times, then add the remaining vulcanizer, and turn over three times. Roll 6 times and take off the sheet. After standing for 16 hours, perform the vulcanization curve test.

[0124] Through the rotorless vulcanizer test, it was determined that when the vulcanization temperature was 175°C, t 10 =0.58min, t 90 =6.57min, Figure 1 It is the vulcanization curve of the rubber compound obtained after plastication on the open mill. Vulcanize in a flat vulcanizer for 8.57 minutes, let stand for 4 hours, perform a second stage vulcanization at 150℃×4 hours, take out the rubber compound, and let stand at room temperature for 16 hours. Cut the rubber compound into dumbbell-shaped specimens and conduct relevant performance tests according to "HG / T2701-2016 Compression Packer Rubber Cylinder". The test results are shown in Table 10.

[0125] Table 10 Physical properties test results of the rubber compound of Example 9

[0126]

[0127] Table 10 is the test results of the physical properties of the rubber mix of Example 9. Compared with Example 1, after the antioxidant is changed to RD(TMQ) / SP=1 / 2, the compression permanent deformation performance of the rubber mix is ​​further optimized, and various performance indicators meet the requirements.

[0128] Example 10

[0129] 100 parts of hydrogenated nitrile rubber, 70 parts of carbon black N220, 2 parts of antioxidant (RD(TMQ) / SP=1 / 3), 0.5 parts of plasticizer dioctyl terephthalate (DOTP), 6.5 parts of peroxide curing agent di-tert-butyl peroxide isopropylbenzene (BIPB).

[0130] Sample preparation:

[0131] Use a 200mL internal mixer, adjust the starting temperature to 50°C and the speed to 40rpm. Lift the top plug, add the hydrogenated nitrile rubber within 15 seconds, close the top plug, and mix for 60 seconds. Lift the top plug, add 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Lift the top plug again, add the remaining 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Mix for another 60 seconds, discharge the rubber, and obtain the rubber compound.

[0132] Take out the rubber compound from the internal mixer and weigh it. Compare it with the total mass of all raw materials added to the internal mixer. The rubber compound loss should be controlled within 3%. Adjust the roller temperature of the open mixer to 45°C and the roller distance to 1.0mm. Plasticize the rubber compound taken out from the internal mixer to make it into sheets, and then adjust the roller distance to 0.12mm. First, turn over three times, add 1 / 2 equivalent vulcanizer, turn over three times, then add the remaining vulcanizer, and turn over three times. Roll 6 times and take off the sheet. After standing for 16 hours, perform the vulcanization curve test.

[0133] Through the rotorless vulcanizer test, it was determined that when the vulcanization temperature was 175°C, t 10 =0.58min, t 90 =6.60min, Figure 1 It is the vulcanization curve of the rubber compound obtained after plastication on the open mill. Vulcanize in a flat vulcanizer for 8.60 minutes, let stand for 4 hours, perform a second stage vulcanization at 150℃×4 hours, take out the rubber compound, and let stand at room temperature for 16 hours. Cut the rubber compound into dumbbell-shaped specimens and perform relevant performance tests according to "HG / T2701-2016 Compression Packer Rubber Cylinder". The test results are shown in Table 11.

[0134] Table 11 Physical property test results of the rubber compound in Example 10

[0135]

[0136]

[0137] Table 11 is the test results of physical properties of the rubber compound of Example 11, and all performance indicators meet the requirements.

[0138] It can be seen from Example 1, Comparative Example 1, and Examples 9-10 that when only SP is used as an antioxidant, the physical properties of the rubber mix decrease, and even some properties (compression set) do not meet the standard requirements. When only RD (TMQ) is used as an antioxidant, the test results meet the relevant standard requirements. When a mixed antioxidant is used, when RD (TMQ) / SP = 1:1, its compression set performance is not as good as using RD (TMQ) alone as an antioxidant, but when RD (TMQ) / SP = 1:2, relative to RD (TMQ) and SP alone as antioxidants, the compression set performance is significantly improved, that is, although SP as an antioxidant has relatively poor performance, it can improve product performance when used in conjunction with RD (TMQ) in a specific ratio, and the performance cannot be improved by an improper ratio. By optimizing the ratio, it is found that when RD (TMQ) / SP = 1:2, the performance of the rubber mix is ​​the best. The main reason may be that both antioxidants are "free radical termination type" antioxidants, and a synergistic anti-aging effect occurs during use, thereby reducing compression set.

[0139] Comparative Example 2

[0140] 100 parts of hydrogenated nitrile rubber, 70 parts of carbon black N220, 2 parts of antioxidant RD (TMQ), 0.5 parts of plasticizer dioctyl terephthalate (DOTP), and 6.5 parts of peroxide curing agent di-tert-butyl peroxide isopropylbenzene (BIPB).

[0141] Sample preparation:

[0142] Use a 200mL internal mixer, adjust the starting temperature to 50°C and the speed to 40rpm. Lift the top plug, add the hydrogenated nitrile rubber within 15 seconds, close the top plug, and mix for 60 seconds. Lift the top plug, add 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Lift the top plug again, add the remaining 1 / 2 equivalent of carbon black, antioxidant, and plasticizer in sequence within 30 seconds, close the top plug and mix for 60 seconds. Mix for another 60 seconds, discharge the rubber, and obtain the rubber compound.

[0143] Take out the rubber compound from the internal mixer and weigh it. Compare it with the total mass of all raw materials added to the internal mixer. The rubber compound loss should be controlled within 3%. Adjust the roller temperature of the open mixer to 45°C and the roller distance to 1.0mm. Plasticize the rubber compound taken out from the internal mixer to make it into sheets, and then adjust the roller distance to 0.12mm. First, turn over three times, add 1 / 2 equivalent vulcanizer, turn over three times, then add the remaining vulcanizer, and turn over three times. Roll 6 times and take off the sheet. After standing for 16 hours, perform the vulcanization curve test.

[0144] Through the rotorless vulcanizer test, it was determined that when the vulcanization temperature was 175°C, t 10 =0.58min, t 90=6.77min, Figure 1 It is the vulcanization curve of the rubber compound obtained after plasticating on the open mill. After vulcanization on the flat plate vulcanizer for 8.77 minutes (no second stage vulcanization), the rubber compound was taken out and left to stand at room temperature for 16 hours. The rubber compound was cut into dumbbell-shaped specimens and relevant performance tests were carried out according to "HG / T 2701-2016 Compression Packer Rubber Cylinder". The test results are shown in Table 12.

[0145] Table 12 Comparative Example 2 Rubber Mix Physical Properties Test Results

[0146]

[0147] Table 12 is the test results of physical properties of the rubber mix of Example 2. Since no two-stage vulcanization was performed, compared with Example 1, some properties (change rate of elongation at break after hot air aging and compression permanent deformation) could not meet the standards, indicating that two-stage vulcanization is crucial to the experimental process.

Claims

1. A rubber material, characterized in that: The invention comprises, by weight: 100 parts of hydrogenated nitrile rubber, 60-70 parts of carbon black, 2 parts of antioxidant, 0.5 parts of plasticizer and 6.5-7.0 parts of peroxide vulcanizer; the antioxidant is RD (TMQ) or a mixture of RD (TMQ) and styrenated phenol.

2. The rubber material according to claim 1, characterized in that: When the antioxidant is a mixture of RD (TMQ) and SP, the ratio of RD (TMQ) to SP is 1:

2.

3. The rubber material according to claim 1, characterized in that: The carbon black is carbon black N220.

4. The rubber material according to claim 1, characterized in that: The plasticizer is dioctyl terephthalate.

5. The rubber material according to claim 1, characterized in that: The peroxide curing agent is di-tert-butyl peroxide isopropylbenzene.

6. The method for preparing the rubber material according to any one of claims 1 to 5, characterized in that: include: Mixing hydrogenated nitrile rubber; adding part of carbon black, part of antioxidant and part of plasticizer, and mixing; Add the remaining carbon black, antioxidant and plasticizer, mix and discharge the rubber to obtain a rubber compound; The rubber material is plasticized; a portion of the peroxide vulcanizer is added and plasticized; and the remaining vulcanizer is added and plasticized; The plasticized rubber compound undergoes one-stage vulcanization and two-stage vulcanization.

7. The method for preparing the rubber material according to claim 6, characterized in that: The vulcanization time is 8.77 to 10.77 minutes.

8. The method for preparing the rubber material according to claim 6, characterized in that: The plasticizing temperature is 45-50°C.

9. The method for preparing a rubber material according to claim 6, characterized in that: The plasticized rubber compound is subjected to a vulcanization curve test, and the plasticized rubber compound is subjected to a stage of vulcanization according to the test result.

10. A packer rubber cartridge, characterized in that: The material is the rubber material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method of reinforced hydrogenated butyronitrile composite material

    CN103589027A

  • Casual shoe soles and preparation method thereof

    CN111154217A